Bloomsbury Dictionary of Science for Everyone - Schneider, Herman and Schneider, Leo (London Bloomsbury, 1990)
Electricity, microwaves, X-rays, computers, television - even the weather forecast - are examples of the science and technology which surround us all. This layman's guide comprises explanations of more than 1000 scientific terms, arranged in A-Z format
Include Picture
Keywords: Science